Technical Efficiency of Irrigated and Rain-fed Rice Farms in North Sumatra, Indonesia - Simatupang, Jones; Nababan, Manaor Bismar Posman (PT. Riset Press International, 2023)
The present paper compares the efficiency of irrigated and rain-fed farming in North Sumatra using a household farm survey for the 2022 growing season. The authors use the Data Envelopment Analysis (DEA) model, mean difference test, and Tobit regression. Empirical results reveal that irrigated farming is more efficient than rain-fed based on CRS and SE assumptions. However, access to irrigation was found to harm rice farming efficiency. Unequal distribution of water, scarcity of water during the growth period, and excess water during the harvest cause a decrease in the efficiency of irrigated farming. The age of the head of household, education, and access to credit was also found to harm technical efficiency. In contrast, the experience variable in participating in farmer groups because it has a positive impact on the efficiency of rice farming. The results provide valuable insights for transforming water management and strengthening the need for investment in irrigation infrastructure as a poverty alleviation mechanism and means to achieve rice farming sustainability in North Sumatra.